Youth in regime crisis comparative perspectives from Russia to Weimar Germany - Krawatzek, Félix 1984- (Oxford studies in democratization, 2018)
This volume provides a comparative study of the discourse around 'youth' and the political mobilization of young people in key moments of crisis in Europe